A experiência da educação profissional para egressas atendidas pelo PRONATEC - Rosa Junior, Paulo Cesar Fernandes da (2017)
This research was developed within a qualitative approach and it aims to reflect about the experience of young people who made a technical course simultaneously the regular high school. The participants of this study are former professional education students who participated of the National Program of Access to Technical Education and Employment (PRONATEC). This investigation attempts to analyze the students’ experiences through their narratives about what has been lived and their perspectives. The research is based on a pragmatic phenomenological approach, centered in John Dewey’s philosophy. The choice is justified by the approximation of Dewey’s theories with theoretical aspects of the professional education. The data were collected through semi structured interviews made in virtual environment. The analysis showed some professional education particularities, such as the appearing of symbolic referentiality, which connects concepts to relevant aspects of subjects’ experiences and professional education properties. These characteristics reflects the bonds among job market demands and the industrialist ideals of the participants. The reflections raised from this investigation aims to point out the need to create new public policies which connect education, youth and the world of work.